Executive-Legislative Relations and Local Government Administration in Nigeria’s Fourth Republic - Cletus Chuck, Egugbo; Oluwaseun Adewale, Salako (Journal of Governance and Public Affairs, 2026)
The patterns of interactions and relationships that exist within any local government administration usually have a significant effect on such local governments. This paper examined the nature of relationships and causes of conflict between the executive and legislative arms of the local government. A structured questionnaire was used to obtain data from 90 respondents drawn from the executive and legislative members of Ndokwa West local government council in Delta State. Simple percentages and tables were used to analyze the data collected. The study concluded that local communities gain more from a cordial relationship between the executive and legislative arms and also tend to suffer if there is a frosty and acrimonious relationship between the legislative and executive arms of government. This paper also recommended that the separation of powers principle should be encouraged, along with checks and balances. Good communication skills should also be encouraged to avert executive-legislative conflict.